PENGARUH FINANCIAL LITERACY, HEDONIC LIFESTYLE, DAN INTENSITAS PENGGUNAAN QRIS TERHADAP PERILAKU KEUANGAN PRIBADI GENERASI Z DI ERA CASHLESS SOCIETY MAHASISWA PRODI MANJEMEN, FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Zuliyana Zuliyana; Ida Ayu Sri Brahmayanti (Jurnal Ekonomi dan Bisnis, 2026)
This study examines the influence of financial literacy, hedonic lifestyle, and QRIS usage intensity on the personal financial behavior of Generation Z students at Universitas 17 Agustus 1945 Surabaya in the cashless society era. The research employed a quantitative approach using a survey method with questionnaires distributed to 100 respondents. Data were analyzed using multiple linear regression with SPSS version 26. The results show that financial literacy and QRIS usage intensity have a significant effect on personal financial behavior, while hedonic lifestyle does not show a significant influence. These findings indicate that financial knowledge and digital payment technology play a dominant role in shaping the financial behavior of Generation Z. The study highlights the importance of strengthening financial education and digital literacy among students.